Periodontal Diseases and Dental Caries in Children with Type 1 Diabetes Mellitus - Marta Novotna; Stepan Podzimek; Zdenek Broukal; Erika Lencova; Jana Duskova (Mediators of Inflammation)
Type 1 diabetes mellitus is a chronic metabolic disease of an autoimmune origin with early manifestation predominantly in the childhood. Its incidence has been rising in most European countries. Diabetes has been intensively studied by all branches of medicine. There were a number of studies investigating oral consequences of diabetes; however, unambiguous conclusions were drawn only for the relationship between diabetes and periodontal impairment. Many studies confirmed higher plaque levels and higher incidence of chronic gingivitis both in adults and in children with diabetes. Juvenile periodontitis is rare both in healthy subjects and in those with type 1 diabetes. Yet certain findings from well-conducted studies, for example, differences in oral microflora or the impact of metabolic control of diabetes on periodontal health, indicate a higher risk of periodontitis in children with type 1 diabetes. As for the association of diabetes and dental caries, the results of the studies are inconsistent. However, it was found that some risk factors for dental caries are either more or less prevalent in the diabetic population. Despite an extensive research in this area we have to acknowledge that many questions have remained unanswered. There is a need for continued, thorough research in this area.